1985
DOI: 10.1104/pp.77.2.509
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Metabolism of Chlamydomonas reinhardtii

Abstract: ABSTRACIEvidence is presented to substantiate a chloroplastic respiratory pathway in the green alga, Chlamydomonas reinhardtii, whereby reducing equivalents generated during the degradation of starch enter the thylakoidal chain at the plastoquinone site catalyzed by NADH-plastoquinone reductase. In this formulation, the reduced plastoquinone is oxidized either by the photoevolution (photosystem I) of H2 under anaerobic conditions or by 02 during dark respiration.In the preceding paper (7), we reported on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…This process involves oxygen-dependent electron flow via the PQ pool and may utilize the same or a similar antimycin A-sensitive component as cyclic electron transport around PSI (Ravenel and Peltier, 1991). Chlororespiration was first studied in green algae (Bennoun, 1982;Gfeller and Gibbs, 1985) and has since been reported in brown algae and higher plants (Owens, 1986b;Caron et al, 1987;Garab et al, 1989). Although past studies have shown that chlororespiration results in the dark reduction of the PQ pool (Bennoun, 1982), these studies did not consider the effects of transthylakoid proton gradient formation that would accompany this electron flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves oxygen-dependent electron flow via the PQ pool and may utilize the same or a similar antimycin A-sensitive component as cyclic electron transport around PSI (Ravenel and Peltier, 1991). Chlororespiration was first studied in green algae (Bennoun, 1982;Gfeller and Gibbs, 1985) and has since been reported in brown algae and higher plants (Owens, 1986b;Caron et al, 1987;Garab et al, 1989). Although past studies have shown that chlororespiration results in the dark reduction of the PQ pool (Bennoun, 1982), these studies did not consider the effects of transthylakoid proton gradient formation that would accompany this electron flow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chlororespiratory electron flow involves the donation of electrons from a membrane-bound NADP(H)-oxidoreductase to the PQ pool and the formation of a transthylakoid proton gradient (Bennoun, 1982;Gfeller and Gibbs, 1985;Garab et al, 1989;Wilhelm and Duval, 1990). Chlororespiration has been reported in higher plants as well as green and brown algae (Gfeller and Gibbs, 1985;Caron et al, 1987;Garab et al, 1989;Wilhelm and Duval, 1990). In cyanobacteria, both photosynthetic and respiratory electron transport pathways intersect at the site of the PQ pool (Dominy and Williams, 1987).…”
mentioning
confidence: 99%
“…Although we have provided evidence of a reductive pathway from OAA to succinate in this alga during anaerobiosis, we do not know the relative flux of carbon between the oxidative and reductive paths of the TCAC. We therefore do not know the significance of the reductive pathway in the maintenance of oxidative TCAC carbon flow relative to other potential processes such as H2 evolution (9,10 (16) and in Euglena (27). It has been shown that fumarate reduction may be linked to NADH oxidation and ATP synthesis (7 and references therein) thereby providing an excellent strategy for anaerobic fermentation.…”
Section: Reductive Tcac Carbon Metabolism During Anaerobiosismentioning
confidence: 99%
“…The yields of acetate and ethanol, two major compounds of starch breakdown in the dark, were strikingly diminished during exposure to illumination, whereas CO2 evolution was enhanced by illumination. Evidence was presented in a more recent paper (15) to substantiate a chloroplastic respiratory pathway in C. reinhardii whereby reducing equivalents generated during starch breakdown were eliminated as H2 rather than coupled to the reduction of acetyl * CoA to ethanol. To account for the low yield of acetate and ethanol, we (14,15) postulated that acetate or the intermediate acetyl * CoA formed during the anaerobic photodissimilation of starch was converted to undetermined cellular material.…”
mentioning
confidence: 99%